ANALISIS EFEKTIVITAS KINERJA PENDAPATAN (STUDI KASUS PADA DINAS PARIWISATA DAN KEBUDAYAAN KABUPATEN BOLAANG MONGONDOW TAHUN 2016-2018) - Buntuan, Dhifa N.; Saerang, David P.E.; Gamaliel, Hendrik (Universitas Sam Ratulangi, 2019)
In Bolaang Mongondow Regency, locally –generated revenue is still considered low and has not a significant increase. One of the SKPD producing PAD is the Tourism and Culture Office. In 2018, Tourism and Culture Office has not yet reached the target. This study aims to: (1) analyze the causes of revenue realization that does not reach the target, and (2) analyze the effectiveness of revenue performance. The research method used is quantitative descriptive. The type of data used qualitative is an explanation of interviews and quantitative data in a budget realization reports and ticket inventory reports for 2016-2018. Data collection methods used interview and documentation. The results showed, the factors causing the realization of revenue that did not reach the target due to the excessively high income target charged to the Office, while managed revenue sources were very limited. The effectiveness of the performance shows, in 2016 and 2017 are very effective category which reached 113.29% and 102.93%. While in 2018, included ineffective category that is 69.92%. It is recommended that the Office further optimizes its financial management so that it focuses on adding new tourism objects so that whatever targets are set can be achieved and can increase the effectiveness of its revenue performance.